IMAN DAN TAQWA BAGI GURU BIMBINGAN DAN KONSELING - Wahyudi, Amien (JURNAL FOKUS KONSELING, 2016)
Faithful and devoted to God Almighty is the obligation to humans , especiallycounselors. With the faith and piety in the counselor, the counselor can carry outtheir duties responsibly. The concept of faith and piety should ideally be returnedto the holy book. Because in the holy book Al Quran in particular the concept offaith and piety have explained So, holy book Al Quran as a source of informationbecause the information comes from al quraan quality absolute meaning that it iscertainly true, because the Quran sent down by Allah for the guidance of mankindKeywords: Faith, god fearing and Al- Quran